The Roles of Digital Application Innovates Student Academic in Higher Education - Herlan Suherlan; Abd. Basir; Abdul Wahab Syakhrani; Besse Arnawisuda Ningsi; Nofirman Nofirman (Nazhruna: Jurnal Pendidikan Islam, 2022)
Abstract This research examines students' efforts to improve academic achievement in higher education the research method used in literature. The literature used comes from books and national and international journals. The results of this study indicate that for students, the application of digital technology to improve student academic achievement can innovate and change student learning achievement so that it is in line with the goals and ideals of the nation. For further research, it is hoped that field studies can prove that students' academic achievement by relying on the internet is only honed from their cognitive abilities without understanding what they take on the internet.